2016
DOI: 10.1111/dme.13134
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Type 1 diabetes at work among Finnish workers

Abstract: Line managers and colleagues have a remarkable role to play in providing workplace support to workers with Type 1 diabetes. Disclosure of Type 1 diabetes should be encouraged as line managers can provide workers with the right support, implement work adaptations and facilitate job retention. As only half of respondents disclosed their Type 1 diabetes at work, further research is required into the reasons for and consequences of not disclosing a diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
4
14
0
2
Order By: Relevance
“…We also found that receiving respect from one's employer may also encourage disclosure. These findings point to psychosocial work environment factors as important determinants of disclosure, which is consistent with previous studies .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that receiving respect from one's employer may also encourage disclosure. These findings point to psychosocial work environment factors as important determinants of disclosure, which is consistent with previous studies .…”
Section: Discussionsupporting
confidence: 92%
“…We also found that receiving respect from one's employer may also encourage disclosure. These findings point to psychosocial work environment factors as important determinants of disclosure, which is consistent with previous studies [9,10]. Despite the potential benefits of disclosing diabetes, an employee might fear, for whatever reason, that disclosure of diabetes may have unwanted consequences.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On balance, the review showed that disclosure decisions were often precipitated by the climate of the organization. Perceptions that one's organization was supportive predicted disclosure among gay and lesbian employees (Griffith & Hebl, 200l; Ragins & Cornwell, ; Ragins et al, ; Reed & Leuty, ), employees with diabetes (Hakkarainen, Moilanen, Hänninen, Räsänen, & Munir, ), and employees with childhood cancer survivorship (Martinez & Hebl, ).…”
Section: Disclosure In the Workplace: A Review Of What We Knowmentioning
confidence: 99%
“…O potrzebie przekonania pracownika chorującego na cukrzycę, żeby poinformował o tym przełożonego, służbę bhp lub współpracowników, świadczy badanie Hakkarainena i wsp. [39]. Takie postępowanie ułatwia otrzymanie wsparcia społecznego i uzyskanie lepszych możliwości kontroli glikemii w miejscu pracy [39].…”
Section: Wyniki Przegląduunclassified